2017
DOI: 10.5194/acp-17-2865-2017
|View full text |Cite
|
Sign up to set email alerts
|

Improving volcanic ash predictions with the HYSPLIT dispersion model by assimilating MODIS satellite retrievals

Abstract: Abstract. Currently, the National Oceanic and Atmospheric Administration (NOAA) National Weather Service (NWS) runs the HYSPLIT dispersion model with a unit mass release rate to predict the transport and dispersion of volcanic ash. The model predictions provide information for the Volcanic Ash Advisory Centers (VAAC) to issue advisories to meteorological watch offices, area control centers, flight information centers, and others. This research aims to provide quantitative forecasts of ash distributions generat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Daiichi Nuclear Power plant accident in 2011 (Chai et al, 2015). It was then modified to estimate the volcanic ash source strengths, vertical distribution, and temporal variations by assimilating MODIS satellite retrievals of volcanic ash clouds while using ash cloud top height information as well (Chai et al (2017). It was found that simultaneously assimilating observations at different times produces better hindcasts than only assimilating the most recent observations.…”
Section: Overviewmentioning
confidence: 99%
“…Daiichi Nuclear Power plant accident in 2011 (Chai et al, 2015). It was then modified to estimate the volcanic ash source strengths, vertical distribution, and temporal variations by assimilating MODIS satellite retrievals of volcanic ash clouds while using ash cloud top height information as well (Chai et al (2017). It was found that simultaneously assimilating observations at different times produces better hindcasts than only assimilating the most recent observations.…”
Section: Overviewmentioning
confidence: 99%
“…To generate the VAAs and VAGs, the VAACs use both observations and modelling systems. Atmospheric dispersion models, initialized with a set of source terms that describe the release of ash into the atmosphere, are used to forecast the onwards transport and deposition of the ash cloud (e.g., [5][6][7][8][9][10][11]). Numerical Weather Prediction (NWP) models are used to simulate the atmospheric conditions and provide the meteorological fields needed to drive the dispersion model.…”
Section: Introductionmentioning
confidence: 99%
“…Another active field for STE applications is the estimation of the volcanic ash emissions. Many attempts have been made for several major volcano eruptions (Wen and Rose, 1994;Prata and Grant, 2001;Wilkins et al, 2014Wilkins et al, , 2016Chai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Reanalysis (NARR) at 32-km (Mesinger et al, 2006 To avoid running the HYSPLIT modeling repeatedly, a TCM is generated similar to the previous HYSPLIT inverse modeling 5 studies (Chai et al, 2015(Chai et al, , 2017. As described in Draxler and Rolph (2012), independent simulations are performed with a unit emission rate from each source location and a pre-defined time segment.…”
mentioning
confidence: 99%